Analysis of pork price fluctuations during the special era when African swine fever and COVID-19 epidemic coexisted: an empirical study in Macau, China - Xu, Fang; Ni, Xiaoyong; Liu, Kai; Wang, Ming; Tan, Kangye; Hu, Jun (Frontiers in Sustainable Food Systems, 2024)
Introduction Emergent crises can have a catastrophic impact on regional economic systems. The concurrent outbreaks of African Swine Fever (ASF) and the COVID-19 pandemic have severely affected Macau’s pork industry, making it an interesting case study for analyzing the effects of simultaneous emergent crises on food prices. Methods The study utilized a comprehensive dataset spanning from March 30, 2018, to April 15, 2022. The analysis employed the Ensemble Empirical Mode Decomposition (EEMD) method to decompose the pork price data into high-frequency, low-frequency, and trend components, while the Bai-Perron test pinpointed key events and regulatory interventions affecting pork prices. Results The findings revealed that short-term market fluctuations had a limited impact on pork price dynamics, with primary drivers being long-term and low-frequency emergencies. The Bai-Perron test identified four significant emergencies or regulatory policies as critical turning points, segmenting the price series into five distinct phases. The results highlight the importance of considering long-cycle emergencies when assessing their impact on food prices and underline the need for more resilient agricultural supply chains. Discussion The study provides insights into how compounded emergent crisis threats impact market behavior and offers policy recommendations for enhancing market stability. Recommendations include strengthening cross-regional epidemic control, investing in vaccine research, optimizing cold chain logistics, updating legal frameworks, and improving emergency preparedness. The implications of these findings are relevant for similar regions facing concurrent health and economic crises, contributing to a better understanding of crisis management and market stability maintenance.